Equity, Diversity, and Community as the Basis for Critical Zone Science and Education. Issue 2 (25th January 2023) - Perdrial, J. N.; Kincaid, D. W.; Wheaton, D.; Seybold, E. C.; Stewart, B.; Walls, L.; Blouin, M.; Toolin, R.; Chorover, J.; Lewis, C.
Abstract: Responding to the social and environmental challenges of the Anthropocene requires that we integrate science across multiple perspectives, approaches, and disciplines in equitable and culturally responsive ways. While critical zone (CZ) science has made large strides in bridging natural, social, and education science disciplines, the field has been slower to address the lack of diversity, especially in terms of "race" and ethnicity. This means that CZ science and education do not fully reflect all communities they must serve, and representation and access to careers in the field therefore remain limited to mostly white individuals. Despite best intentions, predominantly white science and education teams frequently consider values such as diversity, equity, or inclusion in later stages of work instead of centering these values as the foundation from the outset. Here, we reflect on how our CZ Collaborative Network Project has both struggled with, and is learning to, authentically center and uphold our values in our own work. Our goal is to normalize the concept that culturally responsive CZ science and education requires intentional trust and relationship building, flexibility, and continued learning. To support our evolving work, we have relied on team science practices, and we offer insights into the strategies and tools that help us with our aspiration to center and integrate our values of diversity, equity, and community into team processes. Key Points: To address low "racial" and ethnic diversity in critical zone science, we must center diversity, equity, and community at the outset of work This work requires intentional and continuous learning and flexibility, as well as a willingness to step out of one's comfort zone Team science practices and tools can help put these values in practice and offer support when (not if) we fall short